Targeted Change: Using Behavioral Segmentation to Identify and Understand Plastic Consumers and How They Respond to Media Communications. Issue 8 (17th November 2021) - Borg, Kim; Lindsay, Jo; Curtis, Jim
ABSTRACT: To address the global problem of single-use plastic waste, tailored behavior change interventions need to be developed which respond to the way different audiences think and act. The current study adopted a behavior-based segmentation approach, underpinned by the theory of normative social behavior and empirical testing, to better understand plastic consumption and the effect of existing media communications. Using a sample of 1001 respondents, Two-Step Cluster Analysis identified two key consumer types: "Plastic Avoiders" and "Plastic Users." The two groups differed significantly on demographic characteristics, media use/exposure, and theoretical constructs. The most important predictors of group membership were self-efficacy and work status. An experiment involving pre-existing environmental media communications revealed that perceptions, intentions, and behaviors were influenced differently across the two audiences. The findings suggest that mobilizing existing media content may provide a cost-effective way for environmental communicators to increase their public impact while avoiding unintended consequences.